KURIKULUM TERPADU PENDIDIKAN AGAMA ISLAM(DI PONDOK PESANTREN AL-IMAN TEBELIAN KABUPATEN SINTANG) - Adi Subowo; Hifza Hifza; Ubabuddin (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
The objectives of the research were : (1) to Know the concept of integrated curriculum in Al- Iman boarding school, Tebelian Kabupaten Sintang (2) to Know the Implementation of integrated curriculum Al-Iman boarding school, Tebelian Kabupaten Sintang (3) to Know the evaluation of integratedcurriculum at Al-Iman boarding school, Tebelian Kabupaten Sintang. To achieve these objectives, The researcher used field research methods (field research) that is qualitative. In data collection, the presence of the researcher is known by informant. curriculum on Islamic Religion Madrasah Aliyah level in Al- Iman boarding school, Tebelian Kabupaten Sintang include (a) The basic idea of integrated curriculum planning began from the adoption Kulliyatul Mu curriculum "allimin al-Islamiyah (KMI) Gontor and Arrisalah Ponorogo (b) in thepreparation of integrated curriculum lesson materials, determined by the internal MGMP team based on the mission vision of Al-Iman boarding school, Tebelian Kabupaten Sintang. (c) The formulation of curriculum content or content is in accordance with the Standards of Content and Standards of Graduate Competence in accordance with the guideline for the preparation of the Unit Level Curriculum. The Second Implementation of integrated curriculum Pondok Pesantren Modern Al-Iman Pacitan, the stages included (a) Waka Curriculum made the initial steps to determine the curriculum structure based on the students‟ need in the short, term medium and long term. (b) designate the MGMP Coordinator as a controller of KBM and student learning progress (c) The MGMP team played an important role in observing the KBM process by making important records as curriculum improvement modal and coordinating. The third Evaluation used for measure the level of students‟ ability in a chieving the minimum criteroa of completenes (KKM). Defermiming the students‟ success by (a) looking at the daily and weekly value. Based on (b) the value of the semester exams‟ result that are diveded into written and oral exams.